A Pilot Study of a Chronic Pain Self-Management Program Delivered by Community Health Workers to Underserved African American Older Adults. Issue 12 (29th March 2021) - Janevic, Mary; Robinson-Lane, Sheria G; Murphy, Susan L; Courser, Rebecca; Piette, John D
Abstract: Objective: African American older adults living in disadvantaged communities are disproportionately burdened by disabling pain. To address their needs, we tested the feasibility and potential effects of a cognitive-behavioral chronic pain self-management program delivered by community health workers. Design: A single-group, pre-post evaluation of the STEPS-2 (S eniors using T echnology to E ngage in P ain S elf-management) intervention, in which participants learned pain-management skills through web-based videos. They were also given wearable activity trackers to facilitate incremental increases in walking. In weekly telephone calls, community health workers helped participants apply skills and set goals. Subjects/setting: Thirty-one adults in Detroit, Michigan (97% African American, 97% female, mean 68.7 years), with chronic musculoskeletal pain. Methods: Participants completed telephone surveys at baseline and eight weeks. We measured changes in PROMIS pain interference and pain intensity, as well as Patient Global Impression of Change in pain and functioning. Feasibility indicators included participant engagement and satisfaction, and fidelity to session protocols by community health workers. Results: Participants on average completed 6.6/7 sessions, and 100% agreed or strongly agreed that they improved their understanding of pain management. Average community health worker fidelity score was 1.79 (0 to 2 scale). Pain interference decreased from baseline to post-program (T-score 61.6 to 57.3, P =.000), as did pain intensity (0 to 10 scale, 6.3 to 5.1, P =.004). Approximately 90% of participants reported that pain and function were at least "a little better" since baseline. Conclusions: An intervention combining mobile health tools with support from community health workers holds promise for improving pain outcomes among underserved older adults.